O semanário Bundas e o jornalismo econômico - Taveira, Caroline Gonçalves [UNESP] (2014)
This dissertation analyzes the ways of exercising economic journalism, aiming to show how this can become understandable to any readership. Throughout the chapters, among theories and analyzes, seek denote as the alternative media can help facilitate economic understanding information and leave it to the understanding not only of people involved in the economic universe, as well as those readers who are unfamiliar with the jargon economic journalism. By the above, we have seen in the weekly Bundas, considered alternate periodic and circulated in the late 1990s, a medium that facilitated the reading of the texts on economics. Starding from a textual study, inspired by the Content Analysis Bardin, the aim of the paper is to show that it is possible to perform the practice of economic journalism under the alternative point of view, showing that these can bring information to the public in a much more attractive way player and understandable than the big print media